The Mediation Effect of Coping Style on the Relations between Personality and Life Satisfaction in Chinese Adolescents - Xu, Le; Liu, Ru-De; Ding, Yi; Mou, Xiaohong; Wang, Jia; Liu, Ying (Frontiers in Psychology, 2017)
Previous findings showed the associations between each of the Big Five personality trait and adolescents’ life satisfaction were different. Some traits (extraversion and neuroticism) correlated with adolescents’ life satisfaction, while other traits did not have the same associations with adolescents’ life satisfaction. In order to explain why the Big Five traits differed in their associations with adolescents’ life satisfaction, the present study verified the relations between each of the Big Five personality traits and life satisfaction, and demonstrated the mediating effects of coping style on the relations between these personality traits and life satisfaction in a sample of 2,357 Chinese adolescents. The results demonstrated that four of the Big Five personality traits (extraversion, agreeableness, conscientiousness, and neuroticism) had significant associations with life satisfaction. Further, coping style partially mediated the relations between these four traits and life satisfaction, whereas coping style fully mediated the relation between openness to new experience and life satisfaction. The results implied a plausible explanation for why the Big Five traits differed in their associations with life satisfaction found among the previous literature: that there might be some partial or full mediation variables (such as coping style in this study) left unexamined. Theoretical and practical implications of this study on further research and educational practice are discussed.